1331. Pneumococcal Colonization Among Children 5 years of Age and Younger During SARS-CoV-2 Pandemic. (15th December 2022) - Olarte, Liset; Banerjee, Dithi; Swanson, Douglas S; Lee, Brian R; Harrison, Christopher J; Selvarangan, Rangaraj
Abstract: Background: Children ≤5 years of age have the highest rates of pneumococcal colonization and play an important role in the spread of pneumococcus. Our objective was to determine whether the public health measures (physical distancing, masking, and shelter-in-place orders) implemented to slow the spread of SARS-CoV-2 pandemic had an impact on pneumococcal colonization rates among children aged ≤5 years with and without respiratory symptoms during the first year of SARS-CoV-2 pandemic (4/1/20 to 3/31/21). Methods: This is a single center retrospective cohort study. The study period was divided in 3 four-month periods to represent the initial period of strict adherence to public health measures (period 1: Apr-Jul), relaxation of some of these measures (period 2: Aug-Nov) and Northern hemisphere winter season (period 3: Dec-Mar). We used salvaged mid-turbinate samples obtained as part of routine care from patients without respiratory symptoms but screened for SARS-CoV-2 prior to surgery or aerosol generating procedures (asymptomatic) or from patients with respiratory symptoms tested for SARS-CoV-2 and/or other respiratory viruses (symptomatic). Samples were evaluated for pneumococcal colonization by real-time PCR using CDC lytA primers. Sample size was calculated based on the assumption of lower colonization rates in period 1 and gradual increase (10-15%) in the following study periods. Results: A total of 311 patients were included (185 asymptomatic and 126 symptomatic). Demographics, SARS-CoV-2 PCR and pneumococcal colonization results are shown in Table 1. Pneumococcal colonization rates for asymptomatic and symptomatic children were 14% and 22% (p=0.06), respectively. The odds of colonization of asymptomatic children were similar during period 2 (OR 0.96 [95%CI 0.34-2.67]) and period 3 (OR 0.53 [95%CI 0.17-1.62]), using period 1 as reference and after adjusting for age, sex, and SARS-COV-2 results. The odds of colonization of symptomatic children were also similar across the 3 study periods (period 2 OR 1.28 [95%CI 0.41-4.01] and period 3 OR 0.73 [95% CI 0.24-2.18]). Table 1. Characteristics of asymptomatic and symptomatic groups Conclusion: Pneumococcal colonization rates were not significantly impacted by public health measures implemented during the first year of the SARS-CoV-2 pandemic and did not correlate with SARS-CoV-2 positivity. Disclosures: Liset Olarte, MD, MSc, GSK: Grant/Research Support|Merck: Grant/Research Support|Pfizer: Grant/Research Support|Sanofi: Grant/Research Support Douglas S. Swanson, MD, Merck: Grant/Research Support|Pfizer: Grant/Research Support|Sanofi: Grant/Research Support Brian R. Lee, PhD, MPH, CDC: Grant/Research Support|Merck: Grant/Research Support Christopher J. Harrison, MD, Astellas: Grant/Research Support|GSK: Grant/Research Support|Merck: Grant/Research Support|Pediatric News: Honoraria|Pfizer: Grant/Research Support Rangaraj Selvarangan, BVSc, PhD, D(ABMM), FIDSA, F(AAM), BioFire: Grant/Research Support|Luminex: Grant/Research Support.